The Perception of EFL Mahasaraswati Denpasar University Students Toward Code Mixing on Social Media - I Made Yogi Marantika; Putu Tryssa Kirana Sanjiwani; Ida Bagus Gde Nova Winarta (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
This study elaborates with EFL (English Foreign Language) students’ responses on Google Form. This study focused on how to do code mixing and perception of EFL students toward code mixing on social media. Hoffman’s theory (1991) is implemented to compare with students’ responses about how to doing code mixing on social media and Ulya’s formula (2015) is used to analyzed closed questions about perception toward code mixing. To analyzed the data, descriptive qualitative and quantitative methods were used in this study. The data were obtained from an online questionnaire in Google Form. In collecting the data, this study applies an online survey technique. For the data analysis, it was represented using formal and informal methods. The result shows there are 5 similarities between how to students doing code mixing and reason for applying code-mixing from Hoffman’s theory. Whilst, about perception, it was found that students had 15 positive perception, 6 neutral and 4 negatives.